Notes on Bronze Age Flintwork - Dąbrowski, Jan (Analecta Archaeologica Ressoviensia, 2017)
The article is a brief overview of current state of research on the issue of production and use of flint tools in the Bronze Age and at the beginning of the Iron Age in Poland. Both special purpose tools and tools manufactured ad hoc are known to be widely used throughout Bronze Age. Usewear analysis of materials from Poland and Germany made an interesting contribution. Also flint mines were functioning at that time.